Cost-benefit Analysis of an Apple Orchard in the Republic of Srpska - Jalić, Nemanja; PAŽEK, Karmen; VAŠKO, Željko (Agricultura Scientia, 2022)
The aim of this study was to investigate the economic impact of an investment in an apple orchard in the Republic of Srpska, using the cost-benefit analysis method. All investment costs, annual production costs, production volumes and annual revenues were collected through an unstructured survey of the leading fruit production company in the Republic of Srpska "Agroimpex Nova" and based on similar studies from the region on this topic. Investments in fixed assets, materials, services, salaries, loans and depreciation costs were structured and calculated for a period of 15 years. In addition, all quantities produced and other revenues were totaled. Payback period, net present value (NPV) and internal rate of return (IRR) were calculated as the main economic indicators for this production. The total expenditure of the project is €2,836,316 and the net income for 15 years of the project is €5,054,705, so the net cash flow is €2,218,389. The net present value for the assumed discount rate of 6% is €927,691. The net present value per hectare is €46,385. The undiscounted payback period is 7.973 years. At a discount rate of 6%, the payback period is 9.313 years. The internal rate of return is 16.13%. The calculated results suggest that the investment in an apple orchard in the Republic of Srpska is economically feasible and represents an opportunity for future investment in agricultural production.
Keywords: Cost-Benefit analysis; Republic of Srpska